2014
DOI: 10.1073/pnas.1322923111
|View full text |Cite
|
Sign up to set email alerts
|

Odorant receptor-mediated sperm activation in disease vector mosquitoes

Abstract: Insects, such as the malaria vector mosquito, Anopheles gambiae, depend upon chemoreceptors to respond to volatiles emitted from a range of environmental sources, most notably blood meal hosts and oviposition sites. A subset of peripheral signaling pathways involved in these insect chemosensory-dependent behaviors requires the activity of heteromeric odorant receptor (OR) ion channel complexes and ligands for numerous A. gambiae ORs (AgOrs) have been identified. Although AgOrs are expressed in nonhead appendag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
76
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(92 citation statements)
references
References 67 publications
10
76
3
Order By: Relevance
“…Previous studies have indicated orco expression in the testes of these organisms (Pitts et al 2014). AgOrco is localized along the spermatid tails, and treatment with the Orco agonist resulted in the activation and movement of the spermatozoa (Pitts et al 2014).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous studies have indicated orco expression in the testes of these organisms (Pitts et al 2014). AgOrco is localized along the spermatid tails, and treatment with the Orco agonist resulted in the activation and movement of the spermatozoa (Pitts et al 2014).…”
Section: Introductionmentioning
confidence: 94%
“…Thus, it is essential for the functioning of all ORs. Also, Orco plays a critical role in sperm activation in A. Gambea (Pitts et al 2014). The AgOrco is reported to localize along the sperm tail (Pitts et al 2014).…”
Section: Orco Expression Is Elevated In the Head Cyst Cell During Thementioning
confidence: 99%
“…Ocro-specific agnoists, antagonists, as well as other odorant compounds could robustly activate flagella beating. Therefore, chemosensory receptors may mediate sperm activation in insects (Pitts et al 2014). Another study reported that sugar detection is related to ovarian maturation in female Phormia regina (Solari et al 2015).…”
Section: Expression Profilementioning
confidence: 99%
“…Five sugar GRs were first identified from the model insect of Lepidoptera, Bombyx mori (Wanner and Robertson 2008). Since then, a number of lepidopteran sugar GRs were identified and studied (Pitts et al 2014;Zhang et al 2011). Helicoverpa armigera (Hübner) (Lepidoptera: Noctuidae), one of the most destructive agricultural pests, feed on a large number of cultivated crops including cotton, tomato, soybeans, and corn.…”
Section: Introductionmentioning
confidence: 99%
“…However, whether Orco is activated or inhibited, the negative impact on the insect sense of smell, and thus behavior, may well be similar. Additionally, Orco has been shown to be present in the testes and spermatozoa of insects, with Orco agonists and antagonists affecting flagella beating and thus the movement of mosquito spermatozoa (Pitts et al, 2014). These compounds might therefore also directly and broadly interfere with insect reproduction, and by disrupting multiple aspects of the insect life cycle could potentially be very efficient in insect control.…”
Section: Targeting the General Insect Sense Of Smellmentioning
confidence: 99%